A method for preparing CuO / hollow structure CeO2 electrocatalyst and its application
Patent Information
- Application Number
- CN202510189393.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-20
- Publication Date
- 2026-10-20
- Estimated Expiration
- 2045-02-20
AI Technical Summary
[0004]本发明要解决现有电催化CO2还原技术存在的CO2还原产物CH4选择性低、应用的电流密度低的问题,进而提供一种CuO/中空结构CeO2电催化剂的制备方法及应用
[0018]本发明制备的CuO/中空结构CeO2电催化剂表现出优异的电催化CO2还原性能,当其在200mA·cm-2的电流密度下CH4的选择性达到了44%。
Smart Images

Figure CN119932627B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to methods for preparing electrocatalysts and their applications. Background Technology
[0002] Electrocatalytic CO2 reduction technology converts carbon dioxide into useful chemicals and fuels, such as methane and ethylene, through electrochemical reactions. This effectively reduces atmospheric carbon dioxide levels and provides a new approach to the sustainable recycling of energy. The core of this technology lies in developing highly efficient catalysts to improve reaction selectivity and conversion rates.
[0003] In electrocatalytic CO2 reduction, copper (Cu) has been widely studied as a high-performing catalyst. Copper can efficiently reduce CO2 to multi-carbon products such as ethylene and ethanol; however, there is still room for improvement in the activity and stability of pure Cu catalysts. Therefore, many researchers are dedicated to developing novel copper-based composite catalysts to further optimize catalytic performance. However, problems remain, such as low selectivity for the CO2 reduction product CH4 and low current density in practical applications. Summary of the Invention
[0004] This invention aims to address the problems of low selectivity of the CO2 reduction product CH4 and low current density in existing electrocatalytic CO2 reduction technologies, and thus provides a method for preparing CuO / hollow structure CeO2 electrocatalysts and their applications.
[0005] A method for preparing a CuO / hollow structure CeO2 electrocatalyst, comprising the following steps:
[0006] I. Preparation of precursor solution:
[0007] Spherical SiO2 was added to water and ultrasonically dispersed to obtain a SiO2 dispersion. Then, under stirring conditions, cerium salt, precipitant and surfactant were added to the SiO2 dispersion and mixed evenly. Finally, the reaction was stirred at a temperature of 60℃~150℃ for 3h~24h to obtain a precursor solution.
[0008] II. Separation, washing, and drying:
[0009] The precursor solution was sequentially separated, washed, and dried to obtain the precursor.
[0010] III. Roasting:
[0011] The precursor was calcined for 1 to 4 hours in an air atmosphere at a temperature of 200℃ to 600℃ to obtain the precursor SiO2@CeO2.
[0012] IV. Etching:
[0013] The precursor SiO2@CeO2 was added to the etchant and etched for 12h to 36h at room temperature and a rotation speed of 400r / min to 1200r / min. Then it was washed and dried to obtain hollow CeO2 structure.
[0014] V. Impregnation:
[0015] Hollow CeO2 was added to a copper salt solution and stirred. Then, it was calcined at a temperature of 473K to 873K for 3 to 6 hours to obtain a CuO / hollow CeO2 electrocatalyst.
[0016] An application of a CuO / hollow structure CeO2 electrocatalyst: The CuO / hollow structure CeO2 electrocatalyst is used as a raw material to prepare a gas diffusion electrode for electrocatalytic CO2 reduction.
[0017] The beneficial effects of this invention are:
[0018] The CuO / hollow CeO2 electrocatalyst prepared in this invention exhibits excellent electrocatalytic CO2 reduction performance at 200 mA·cm⁻¹. -2 The selectivity of CH4 reached 44% at the specified current density.
[0019] The CuO / hollow CeO2 electrocatalyst prepared by this invention has a simple process, good scalability, and can be produced on a large scale. Attached Figure Description
[0020] Figure 1 XRD images of the hollow CeO2 prepared in step four of Example 1 and the CuO / hollow CeO2 electrocatalyst prepared in step five.
[0021] Figure 2 The image shows a scanning electron microscope image of the hollow CeO2 structure prepared in step four of Example 1.
[0022] Figure 3 Scanning electron microscope image of the CuO / hollow CeO2 electrocatalyst prepared in Example 1;
[0023] Figure 4 XPS image of the CuO / hollow CeO2 electrocatalyst prepared in Example 1;
[0024] Figure 5 The curves showing the selectivity of CO2 reduction products of the CuO / hollow CeO2 electrocatalyst prepared in Example 1 as a function of applied current density are shown. Detailed Implementation
[0025] Specific Implementation Method 1: This implementation method describes a method for preparing a CuO / hollow structure CeO2 electrocatalyst, which is carried out according to the following steps:
[0026] I. Preparation of precursor solution:
[0027] Spherical SiO2 was added to water and ultrasonically dispersed to obtain a SiO2 dispersion. Then, under stirring conditions, cerium salt, precipitant and surfactant were added to the SiO2 dispersion and mixed evenly. Finally, the reaction was stirred at a temperature of 60℃~150℃ for 3h~24h to obtain a precursor solution.
[0028] II. Separation, washing, and drying:
[0029] The precursor solution was sequentially separated, washed, and dried to obtain the precursor.
[0030] III. Roasting:
[0031] The precursor was calcined for 1 to 4 hours in an air atmosphere at a temperature of 200℃ to 600℃ to obtain the precursor SiO2@CeO2.
[0032] IV. Etching:
[0033] The precursor SiO2@CeO2 was added to the etchant and etched for 12h to 36h at room temperature and a rotation speed of 400r / min to 1200r / min. Then it was washed and dried to obtain hollow CeO2 structure.
[0034] V. Impregnation:
[0035] Hollow CeO2 was added to a copper salt solution and stirred. Then, it was calcined at a temperature of 473K to 873K for 3 to 6 hours to obtain a CuO / hollow CeO2 electrocatalyst.
[0036] In this specific embodiment, copper oxide is supported on hollow cerium oxide (H-CeO2), which significantly improves the activity and stability of the catalyst. The hollow structure provides a larger specific surface area and more active sites, while the oxygen storage capacity of H-CeO2 helps to regulate the redox environment during the reaction process, thereby promoting the efficient conduct of the CO2 reduction reaction.
[0037] The beneficial effects of this embodiment are:
[0038] The CuO / hollow CeO2 electrocatalyst prepared in this embodiment exhibits excellent electrocatalytic CO2 reduction performance at 200 mA·cm⁻¹. -2 The selectivity of CH4 reached 44% at the specified current density.
[0039] The CuO / hollow CeO2 electrocatalyst prepared in this embodiment is simple to process, has good scalability, and can be produced on a large scale.
[0040] Specific Implementation Method Two: This implementation method differs from Specific Implementation Method One in that: the particle size of the spherical SiO2 in step one is 100nm to 500nm; the cerium salt in step one is cerium nitrate or cerium chloride; the precipitant in step one is sodium carbonate, sodium bicarbonate, urea, or hexamethylenetetramine; and the surfactant in step one is polyvinylpyrrolidone, N-methylpyrrolidone, octadecyltrimethylammonium bromide, or sodium secondary alkyl sulfonate. Everything else is the same as in Specific Implementation Method One.
[0041] Specific Implementation Method Three: This implementation method differs from Specific Implementation Method One or Two in that: the concentration of spherical SiO2 in the SiO2 dispersion in step one is 0.1 mg / mL to 10 mg / mL; the molar ratio of spherical SiO2 to cerium salt in step one is 1:(0.2 to 1); the molar ratio of spherical SiO2 to precipitant in step one is 1:(0.2 to 1); and the mass ratio of spherical SiO2 to surfactant in step one is 1:(5 to 20). Everything else is the same as in Specific Implementation Method One or Two.
[0042] Specific Implementation Method Four: This implementation method differs from Specific Implementation Methods One to Three in that the separation, washing, and drying described in step two are specifically carried out as follows: Centrifuge at 4000 rpm to 9000 rpm for 2 to 10 minutes to obtain particles; then wash with anhydrous ethanol and water until the foam disappears; finally, dry the washed particles at 40°C to 90°C for 12 to 24 hours. Specifically, the washing and drying in step four involves washing with anhydrous ethanol and water until neutral, then drying at 40°C to 90°C for 12 to 24 hours. The rest is the same as in Specific Implementation Method Three.
[0043] Specific Implementation Method Five: This implementation method differs from Specific Implementation Methods One to Four in that: the mass ratio of the precursor SiO2@CeO2 to the volume ratio of the etchant in step four is 1 g:(30-150) mL; the etchant in step four is a NaOH solution or a KOH solution; and the concentration of the etchant in step four is 1 M to 15 M. Everything else is the same as in Specific Implementation Methods One to Four.
[0044] Specific Implementation Method Six: This implementation method differs from Specific Implementation Methods One to Five in that: the copper salt solution mentioned in step five is a copper chloride solution or a copper nitrate solution; the concentration of the copper salt solution mentioned in step five is 1 mg / mL to 50 mg / mL; and the molar ratio of the hollow CeO2 structure mentioned in step five to the copper salt in the copper salt solution is 1:(0.2 to 2). Everything else is the same as in Specific Implementation Methods One to Five.
[0045] Specific Implementation Method Seven: This implementation method describes the application of a CuO / hollow structure CeO2 electrocatalyst. The CuO / hollow structure CeO2 electrocatalyst is used as a raw material to prepare a gas diffusion electrode for electrocatalytic CO2 reduction.
[0046] Specific Implementation Method Eight: This implementation method differs from Specific Implementation Method Seven in that the gas diffusion electrode is prepared according to the following steps:
[0047] ①The CuO / hollow CeO2 electrocatalyst was added to a mixed solution of Nafion and isopropanol, and ultrasonically mixed for 10 min to 60 min under a power of 100 W to 500 W to obtain catalyst ink.
[0048] The volume ratio of Nafion solution to isopropanol in the Nafion and isopropanol mixed solution is 1:(10-35); the concentration of CuO / hollow structure CeO2 electrocatalyst in the catalyst ink is 3mg / mL to 10mg / mL;
[0049] ②The loading amount of CuO / hollow structure CeO2 electrocatalyst is 0.5 mg / cm³. 2 ~2.0mg / cm 2 The catalyst ink is sprayed onto carbon paper at a temperature of 35℃ to 65℃ and then dried to obtain a gas diffusion electrode. The rest is the same as in Specific Embodiment Seven.
[0050] The preparation of the gas diffusion electrode in this embodiment is simple. The CuO / hollow structure CeO2 electrocatalyst does not require pretreatment. As a stable oxide, the CuO / hollow structure CeO2 electrocatalyst is stable in an air atmosphere, so there is no need to consider the problem of air oxidation.
[0051] Specific Implementation Method Nine: This implementation method differs from Specific Implementation Method Seven or Eight in that the electrocatalytic CO2 reduction is carried out according to the following steps:
[0052] ① Assembly: Using a flow electrolyzer, a gas diffusion electrode is set between the CO2 gas flow chamber and the cathode chamber, and an anion exchange membrane is set between the cathode chamber and the anode chamber; the counter electrode is set in the anode chamber, the reference electrode is set in the cathode chamber, and the cathode liquid flow cell is connected to the cathode chamber through a conduit, and the anode liquid flow cell is connected to the anode chamber through a conduit. The electrolyte is poured into the cathode liquid flow cell and the anode liquid flow cell. Finally, the positive terminal of the power supply is connected to the counter electrode, and the negative terminal of the power supply is connected to the gas diffusion electrode.
[0053] ② Electrocatalytic activation: CO2 gas is introduced into the CO2 gas flow chamber at a flow rate of 1 mL / min to 50 mL / min. CO2 is continuously introduced, and the catalyst is activated for 5 min to 60 min under the condition that the potential of -1.0 V to -3.0 V vs Ag / AgCl is applied to the gas diffusion electrode.
[0054] ③ Electrocatalytic CO2 reduction: CO2 gas is introduced into the CO2 gas flow chamber at a flow rate of 1 mL / min to 50 mL / min, and the CO2 is continuously introduced. The gas diffusion electrode current density is 50 mA·cm⁻¹. -2 ~1A·cm -2 Under the specified conditions, CO2 is reduced by electrocatalysis, the gaseous products are collected, and the electrolyte after the reaction is separated and purified, thus completing the electrocatalytic CO2 reduction. Other aspects are the same as in specific embodiments seven or eight.
[0055] Specific Implementation Method Ten: This implementation method differs from Specific Implementation Methods Seven to Nine in that: the electrolyte in step ① is a KOH electrolyte with a concentration of 0.5M to 3M; the CO2 gas flow chamber in step ① is made of stainless steel; the counter electrode in step ① is foamed Ni, Pt-plated titanium felt, or IrO2-plated titanium felt; and the reference electrode in step ① is an Ag / AgCl electrode. Everything else is the same as in Specific Implementation Methods Seven to Nine.
[0056] The beneficial effects of the present invention are verified using the following embodiments:
[0057] Example 1:
[0058] A method for preparing a CuO / hollow structure CeO2 electrocatalyst, comprising the following steps:
[0059] I. Preparation of precursor solution:
[0060] Spherical SiO2 was added to water and ultrasonically dispersed for 20 min at a power of 300 W to obtain a SiO2 dispersion. Then, cerium salt, precipitant and surfactant were added to the SiO2 dispersion and mixed evenly at a stirring speed of 800 r / min. Finally, the reaction was stirred for 8 h at a temperature of 100℃ and a stirring speed of 800 r / min to obtain a precursor solution.
[0061] II. Separation, washing, and drying:
[0062] The precursor solution was sequentially separated, washed, and dried to obtain the precursor.
[0063] III. Roasting:
[0064] The precursor was calcined for 2 hours in an air atmosphere at a temperature of 400℃ to obtain the precursor SiO2@CeO2.
[0065] IV. Etching:
[0066] The precursor SiO2@CeO2 was added to the etchant and etched for 24 hours at room temperature and a rotation speed of 800 r / min. Then it was washed and dried to obtain hollow CeO2 structure.
[0067] V. Impregnation:
[0068] Hollow CeO2 was added to a copper salt solution and stirred for 180 min at a stirring speed of 800 r / min. Then, it was calcined at 400 °C for 5 h to obtain a CuO / hollow CeO2 electrocatalyst.
[0069] The average particle size of the spherical SiO2 mentioned in step one is 300 nm; the cerium salt mentioned in step one is cerium nitrate; the precipitant mentioned in step one is hexamethylenetetramine; and the surfactant mentioned in step one is polyvinylpyrrolidone.
[0070] The concentration of spherical SiO2 in the SiO2 dispersion in step one is 2 mg / mL; the molar ratio of spherical SiO2 to cerium salt in step one is 1:0.5; the molar ratio of spherical SiO2 to precipitant in step one is 1:0.5; and the mass ratio of spherical SiO2 to surfactant in step one is 1:10.
[0071] The separation, washing, and drying described in step two are carried out in the following steps: centrifuge at 8000 rpm for 5 min to obtain particles, then wash with anhydrous ethanol and water as washing liquid until the foam in the solution disappears, and finally dry the washed particles at 60°C for 12 h; the washing and drying described in step four are carried out with anhydrous ethanol and water as washing liquid until neutral, and then dry at 60°C for 12 h.
[0072] The mass ratio of the precursor SiO2@CeO2 to the volume ratio of the etchant in step four is 1 g: 75 mL; the etchant in step four is a NaOH solution; and the concentration of the etchant in step four is 3 M.
[0073] The copper salt solution mentioned in step five is a copper nitrate solution; the concentration of the copper salt solution mentioned in step five is 10 mg / mL; the molar ratio of the hollow CeO2 structure mentioned in step five to the copper salt in the copper salt solution is 1:0.2.
[0074] The CuO / hollow CeO2 electrocatalyst prepared above is used as a raw material to prepare a gas diffusion electrode for electrocatalytic CO2 reduction.
[0075] The gas diffusion electrode is prepared according to the following steps:
[0076] ① The CuO / hollow CeO2 electrocatalyst was added to a mixed solution of Nafion and isopropanol, and ultrasonically mixed for 20 min at a power of 300W to obtain the catalyst ink.
[0077] The volume ratio of Nafion solution to isopropanol in the Nafion and isopropanol mixed solution is 1:30; the concentration of CuO / hollow structure CeO2 electrocatalyst in the catalyst ink is 7 mg / mL;
[0078] ②The loading amount of CuO / hollow structure CeO2 electrocatalyst is 1.0 mg / cm³. 2 At a temperature of 55°C, catalyst ink is sprayed onto carbon paper and then dried to obtain a gas diffusion electrode.
[0079] The carbon paper is 28BC;
[0080] The electrocatalytic CO2 reduction is carried out according to the following steps:
[0081] ① Assembly: Using a flow electrolyzer, a gas diffusion electrode is set between the CO2 gas flow chamber and the cathode chamber, and an anion exchange membrane is set between the cathode chamber and the anode chamber; the counter electrode is set in the anode chamber, the reference electrode is set in the cathode chamber, and the cathode liquid flow cell is connected to the cathode chamber through a conduit, and the anode liquid flow cell is connected to the anode chamber through a conduit. The electrolyte is poured into the cathode liquid flow cell and the anode liquid flow cell. Finally, the positive terminal of the power supply is connected to the counter electrode, and the negative terminal of the power supply is connected to the gas diffusion electrode.
[0082] The electrolyte is a 1M KOH electrolyte; the CO2 gas flow chamber is made of stainless steel; the counter electrode is foamed Ni; the reference electrode is an Ag / AgCl electrode; and the anion exchange membrane is fumasepFAA-3-PK-130.
[0083] ② Electrocatalytic activation: CO2 gas was introduced into the CO2 gas flow chamber at a flow rate of 30 mL / min. CO2 was continuously introduced, and the catalyst was activated for 20 min under the condition that the potential of -2.0 V vs Ag / AgCl was applied to the gas diffusion electrode.
[0084] ③ Electrocatalytic CO2 reduction: CO2 gas is introduced into the CO2 gas flow chamber at a flow rate of 30 mL / min, and the CO2 supply is maintained continuously. The gas diffusion electrode current density is 50 mA·cm⁻¹. -2 ~300mA·cm -2 Under certain conditions, CO2 is reduced by electrocatalysis, the gaseous products are collected, and the electrolyte after the reaction is separated and purified, thus completing the electrocatalytic CO2 reduction.
[0085] Figure 1 The figures show the XRD images of the hollow CeO2 electrocatalyst prepared in step four of Example 1 and the CuO / hollow CeO2 electrocatalyst prepared in step five. As can be seen from the figures, the system without copper salt impregnation only exhibits relevant diffraction peaks for CeO2. However, the system impregnated with copper salt does not exhibit relevant diffraction peaks for CuO, possibly because the generated CuO particles are too small.
[0086] Figure 2 The image shows a scanning electron microscope image of the hollow CeO2 structure prepared in step four of Example 1. Figure 3 The image shows a scanning electron microscope (SEM) image of the CuO / hollow CeO2 electrocatalyst prepared in Example 1. As can be seen from the image, CeO2 exhibits only a spherical morphology before copper salt impregnation. After copper salt impregnation, the heterogeneous particles observed on the CeO2 surface are the impregnated CuO particles.
[0087] Figure 4The image shows an XPS image of the CuO / hollow CeO2 electrocatalyst prepared in Example 1. As can be seen from the image, no Cu peak was observed in CeO2 before copper salt impregnation. After copper salt impregnation, the presence of +2 valence Cu on the CeO2 surface further indicates the formation of CuO.
[0088] Figure 5 The figure shows the CO reduction product selectivity of the CuO / hollow CeO2 electrocatalyst prepared in Example 1 as a function of applied current density. As can be seen from the figure, with the gradual increase of applied current density, the CO selectivity of the CuO / hollow CeO2 electrocatalyst gradually decreases, while the CH4 selectivity gradually increases. At 200 mA·cm⁻¹, the selectivity reaches a certain level. -2 At a given current density, the selectivity for CH4 reached 44%, indicating that *CO is hydrogenated to form CH4 at high current densities. Meanwhile, as the current density gradually increases, the H2 selectivity shows a trend of first decreasing and then increasing, indicating that at high current densities, *H promotes CH4 formation. Excessive H* readily forms H2, leading to increased H2 selectivity.
Claims
1. A method for preparing a CuO / hollow structure CeO2 electrocatalyst, characterized in that... It is done in the following steps: I. Preparation of precursor solution: Spherical SiO2 was added to water and ultrasonically dispersed to obtain a SiO2 dispersion. Then, under stirring conditions, cerium salt, precipitant and surfactant were added to the SiO2 dispersion and mixed evenly. Finally, the reaction was stirred at a temperature of 60℃~150℃ for 3h~24h to obtain a precursor solution. The spherical SiO2 has a particle size of 100nm~500nm; the concentration of spherical SiO2 in the SiO2 dispersion is 0.1mg / mL~10mg / mL; the molar ratio of spherical SiO2 to cerium salt is 1:(0.2~1); the molar ratio of spherical SiO2 to precipitant is 1:(0.2~1); the mass ratio of spherical SiO2 to surfactant is 1:(5~20). II. Separation, washing, and drying: The precursor solution was sequentially separated, washed, and dried to obtain the precursor. III. Roasting: The precursor was calcined for 1 to 4 hours in an air atmosphere at a temperature of 200°C to 600°C to obtain the precursor SiO2@CeO2. IV. Etching: The precursor SiO2@CeO2 was added to the etchant and etched for 12h to 36h at room temperature and a rotation speed of 400r / min to 1200r / min. Then it was washed and dried to obtain hollow CeO2 structure. The mass ratio of the precursor SiO2@CeO2 to the volume ratio of the etchant is 1 g:(30~150) mL; the etchant is a NaOH solution or a KOH solution; the concentration of the etchant is 1 M~15 M. V. Impregnation: Hollow CeO2 was added to a copper salt solution and stirred. Then, it was calcined at a temperature of 473K~873K for 3h~6h to obtain a CuO / hollow CeO2 electrocatalyst. The copper salt solution is a copper chloride solution or a copper nitrate solution; the concentration of the copper salt solution is 1 mg / mL to 50 mg / mL; the molar ratio of the hollow CeO2 structure to the copper salt in the copper salt solution is 1:(0.2~2); The CuO / hollow CeO2 electrocatalyst described above was used as a raw material to prepare a gas diffusion electrode for electrocatalytic CO2 reduction at 200 mA·cm⁻¹. -2 The selectivity of CH4 at the given current density is 44%.
2. The method for preparing a CuO / hollow structure CeO2 electrocatalyst according to claim 1, characterized in that... The cerium salt mentioned in step one is cerium nitrate or cerium chloride; the precipitant mentioned in step one is sodium carbonate, sodium bicarbonate, urea or hexamethylenetetramine; the surfactant mentioned in step one is polyvinylpyrrolidone, N-methylpyrrolidone, octadecyltrimethylammonium bromide or sodium secondary alkyl sulfonate.
3. The method for preparing a CuO / hollow structure CeO2 electrocatalyst according to claim 1, characterized in that... The separation, washing, and drying described in step two are carried out in the following steps: centrifuge at a speed of 4000 rpm to 9000 rpm for 2 min to 10 min to obtain particles, then wash with anhydrous ethanol and water as washing liquid until the foam in the solution disappears, and finally dry the washed particles at a temperature of 40℃ to 90℃ for 12 h to 24 h; the washing and drying described in step four are carried out by washing with anhydrous ethanol and water as washing liquid until neutral, and then drying at a temperature of 40℃ to 90℃ for 12 h to 24 h.
4. The method for preparing a CuO / hollow structure CeO2 electrocatalyst according to claim 1, characterized in that... The gas diffusion electrode is prepared according to the following steps: ① Add CuO / hollow CeO2 electrocatalyst to a mixed solution of Nafion and isopropanol, and ultrasonically mix for 10 min to 60 min at a power of 100 W to 500 W to obtain catalyst ink; The volume ratio of Nafion solution to isopropanol in the Nafion and isopropanol mixed solution is 1:(10~35); the concentration of CuO / hollow structure CeO2 electrocatalyst in the catalyst ink is 3mg / mL~10mg / mL; ②The loading amount of CuO / hollow structure CeO2 electrocatalyst is 0.5 mg / cm³. 2 ~2.0mg / cm 2 Under conditions of 35℃~65℃, catalyst ink is sprayed onto carbon paper and then dried to obtain a gas diffusion electrode.
5. The method for preparing a CuO / hollow structure CeO2 electrocatalyst according to claim 4, characterized in that... The electrocatalytic CO2 reduction is carried out according to the following steps: ① Assembly: Using a flow electrolyzer, a gas diffusion electrode is set between the CO2 gas flow chamber and the cathode chamber, and an anion exchange membrane is set between the cathode chamber and the anode chamber; the counter electrode is set in the anode chamber, the reference electrode is set in the cathode chamber, and the cathode liquid flow cell is connected to the cathode chamber through a conduit, and the anode liquid flow cell is connected to the anode chamber through a conduit. The electrolyte is poured into the cathode liquid flow cell and the anode liquid flow cell. Finally, the positive terminal of the power supply is connected to the counter electrode, and the negative terminal of the power supply is connected to the gas diffusion electrode. ② Electrocatalytic activation: CO2 gas is introduced into the CO2 gas flow chamber at a flow rate of 1 mL / min to 50 mL / min. CO2 is continuously introduced, and the catalyst is activated for 5 min to 60 min under the condition that the potential applied to the gas diffusion electrode is -1.0 V to -3.0 V vs Ag / AgCl. ③ Electrocatalytic CO2 reduction: CO2 gas is introduced into the CO2 gas flow chamber at a flow rate of 1 mL / min to 50 mL / min, and the CO2 is continuously introduced. The gas diffusion electrode current density is 50 mA·cm⁻¹. -2 ~1A·cm -2 Under certain conditions, CO2 is reduced by electrocatalysis, the gaseous products are collected, and the electrolyte after the reaction is separated and purified, thus completing the electrocatalytic CO2 reduction.
6. The method for preparing a CuO / hollow structure CeO2 electrocatalyst according to claim 5, characterized in that... The electrolyte mentioned in step ① is a KOH electrolyte with a concentration of 0.5M~3M; the CO2 gas flow chamber mentioned in step ① is made of stainless steel; the counter electrode mentioned in step ① is foamed Ni, Pt-plated titanium felt, or IrO2-plated titanium felt; the reference electrode mentioned in step ① is an Ag / AgCl electrode.
Citation Information
Patent Citations
Mesoporous metal oxide hollow material with high specific surface area and preparation method thereof
CN113501548A
CuO-CeO2 nano-catalyst rich in oxygen vacancies, preparation method of CuO-CeO2 nano-catalyst and application of CuO-CeO2 nano-catalyst in electrocatalytic carbon dioxide reduction
CN115627494A
Electrocatalytic reduction system for preparing ethylene by electrochemically reducing carbon dioxide and application of electrocatalytic reduction system
CN119287392A